Learners with dyslexia: Exploring their experiences with different reading affordances. Themes in Science and Technology Education - Special issue on Language Disorders and ICT. - Chen, Chwen Jen; Keong, M.W.; Teh, Chee Siong; Chuah, Kee-Man (Themes in Science and Technology Education, 2015)
To date, empirically derived guidelines for designing accessible online learning environments for learners with dyslexia are still scarce. This study aims to explore the learning experience of learners with dyslexia when reading passages using different online reading affordances to derive some guidelines for dyslexia-friendly online text. The study employed a multiple-case qualitative approach and key themes were interpreted based on these learners’ perceived learning, engagement and satisfaction. The study concludes that the use of screen reader for online reading should be optional, adequate control of screen reader should be provided and screen reader is more beneficial when online text is written in a language that the learner is not proficient. Results from this study also provide empirical support of the appropriateness of some existing web accessibility guidelines.